New campus-Thomas Administration building-0004 (1917)
Nerve Center of a rapidly expanding campus is the Frank W. Thomas Administration Building named for the second president of Fresno State College who served from 1917 to 1948. Development and supervision of instructional programs and maintenance of student records are among the numerous functions concentrated in many offices.